Why am I Not Photogenic? Differences in Face Memory for the Self and others. (May 2014) - Wen, Wen; Kawabata, Hideaki
Many people complain that they do not photograph well. In the present study, we hypothesised that the self-face is memorized more beautifully than reality, which may result in reports of being not photogenic. We took photographs of students who were in the same university course and were familiar with one another. We then magnified or shrunk the size of their eyes (Experiment 1; N = 10) and their mouths (Experiment 2; N = 10). We asked the students to select the picture that seemed most like their classmates' real faces or their own real face. The results showed that there were significant differences between memories of their own and others' faces. Participants selected their classmates' real faces to a greater degree than the modified faces. However, participants tended to select pictures of themselves with magnified eyes and shrunken mouths more often than for their classmates. In Experiment 3 (N = 22), more male participants were included and the influence of gender and mirror-reversed images were examined. We found that there were no significant differences across gender, and the mirror reversal did not change the participants' selections. The bias of self-face recognition may reflect different memory processes for the self and others.